Penguatan Pendidikan Karakter Pada Peserta Didik Dengan Pembelajaran Tahfidz di SMK Muhammadiyah 2 Andong - Alif Andyan; Mohammad Zakki Azani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to describe the strengthening of character education among students through tahfidz learning at SMK Muhammadiyah 2 Andong. This research employed a qualitative descriptive method with data collection techniques consisting of observation, interviews, and documentation. The research subject was an Islamic Religious Education teacher who supervised the tahfidz extracurricular activity in Class X Creative at SMK Muhammadiyah 2 Andong. The study was conducted from July 26 to August 1, 2022. The results showed that the implementation of tahfidz learning was carried out through several stages, including the preparation and selection of instructors, grouping students based on their memorization abilities, conducting muroja’ah and ziyadah activities, and submitting memorization to the supervising teacher. Tahfidz learning also applied methods and habituation activities that supported the process of memorizing the Qur’an. The implementation of character education through tahfidz learning developed several character values in students, namely religiosity, honesty, discipline, reading interest, and responsibility. In addition, evaluations were conducted daily and periodically to determine the development of students’ memorization and behavior. Based on the findings, it can be concluded that tahfidz learning at SMK Muhammadiyah 2 Andong contributes positively to strengthening students’ character education through the habituation of Islamic values in daily life.